Time perspective of forced migrants with different types of socio-psychological adaptation - Maria V. Serebryanaya; Albina A. Buchek (Saratov State University, 2023)
The study is relevant due to the necessity to increase the efficiency of socio-psychological adaptation in connection with the growing number of migrants from other countries. The aim of the study is to determine the features of the time perspective in the course of socio-psychological adaptation of forced migrants. The article hypothesizes that time perspective of forced migrants will vary depending on the type of socio-psychological adaptation and on different stages of adulthood. The study sample includes 36 forced migrants who are staying in the tem-porary accommodation facility in the Belgorod region, aged from 34 to 57 (13 men and 23 women), 21 of them are at the age of early adulthood, 15 are in late adulthood. The methods (tools) of the research are as follows: the "Adaptation of a Personality to a New Socio-Cultural Environment Test" (L. V. Yankovsky) was used to determine the type of adaptation to a new socio-cultural environment; the "Time Perspective Questionnaire" (F. Zimbardo) was applied to study the temporal orientation; a questionnaire was used to fix the socio-demographic status. The study results. At the level of statistical trends, the study proves that early adulthood may be more characterized by an interactive type of adaptation to a new environment, whereas late adulthood may be characterized by a more negative perception of one's past. The results show that beliefs regarding the time perspective, that prevent the development of a sense of acceptance by the new environment and of the confidence in their capabilities, are characteristic of unproductive adaptation types. The study identifies the attitude to one's past and the tendency to fatalism of the present as the most significant components of the time perspective for the adaptation process. The author clarifies specific adaptation types and the category of the "productive/unproductive" adaptation types as a whole. The conclusions. Negative perception of one's past and fatalistic perception of the present are characteristic of unproductive adaptation types (depressive and alienated). A positive attitude to one's past determines the productive course of socio-psychological adaptation. Among the productive adaptation types, a positive attitude characterizes the adaptive type of inclusion in the new socio-cultural environment. Identification of the time perspective features of forced migrants in the course of their socio-psychological adaptation in the context of a short stay in the country determines the novelty of the issue under discussion. The results obtained can be used in the practice of organizing psychological support for the socio-psychological adaptation of forced migrants.